Effect of mechanical aging on the bond strength to dentin of CAD/CAM materials - Branco, Thaís Bulzoni; Vieira Junior, Waldemir Francisco; Lima, Débora Alves Nunes Leite; Marchi, Giselle Maria; Rischka, Klaus; Aguiar, Flávio Henrique Baggio (Brazilian Dental Science, 2026)
Objective: To evaluate the bond strength of different CAD/CAM materials to dentin with and without mechanical aging. Material and Methods: Sixty human dentin specimens (4 mm height) were used, onto which blocks (4 mm height) of the following materials were cemented: fiberglass (FC; FIBER CAD; Angelus), vitroceramic composite (BB; Brava Block; FGM), and polyetheretherketone (PK; PEEK; JUVORA). Half of the specimens for each material were subjected to mechanical aging (n=10). Subsequently, sticks (1×1 mm) were prepared, subjected to the microtensile test (MPa). Then, the fracture pattern was evaluated using a stereoscopic magnifying glass (50×). Additionally, a scanning electron microscope was employed. Data were analyzed using a generalized linear model and Fisher’s exact test (α=0.05). Results: BB exhibited the highest bond strength values (28.39 ± 7.49 MPa without aging; 29.89 ± 7.28 MPa with aging), while FC showed the lowest (18.18 ± 5.26 MPa without aging; 18.46 ± 2.73 MPa with aging) (ρ<0.05), regardless of aging. PK showed intermediate values (24.73 ± 5.17 MPa without aging; 21.89 ± 7.41 MPa with aging). No significant differences were observed between conditions with and without mechanical cycling (ρ>0.05). Conclusion: Within the limitations of this in vitro study, the type of material influenced adhesive performance, while aging did not affect bond strength. FC exhibited the lowest bond strength, with an increase in adhesive failures after aging. KEYWORDS Adhesion; Ceramics; Composite resins; Computer-aided design; Polymers.